Implementasi Program KKN Terintegrasi dalam Penguatan Pendidikan Karakter, Literasi Hukum Haki, Penguatan UMKM, dan Penataan Infrastruktur Sosial di Desa Kembangbelor Kec. Pacet Kab. Mojokerto: Pengabdian - Dewi Ratih Kumalasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Community Service Program (KKN) is a form of implementation of the Tri Dharma of Higher Education that aims to help resolve problems in the community, particularly related to the limited understanding of Micro, Small, and Medium Enterprises (MSMEs) in Dusun Paras regarding legal aspects, especially the difference between Trademark Rights and Patent Rights. The implementation method of the activity uses an integrated approach that combines education, consultation, and mentoring by 15 students from across the faculties of Law, Engineering, Social and Political Sciences, and Economics and Business. The entire work program is based on the Social Learning Theory by Albert Bandura, which emphasizes that individuals learn through observation, imitation, and modeling behavior. This activity involved 14 Micro, Small, and Medium Enterprises (MSMEs) and was proven effective, demonstrated by increased understanding and enthusiasm of residents during the mentoring process. The results of the activity show that the integration of legal education, business literacy, and direct mentoring can strengthen the capacity of residents to protect and develop their businesses. This program also increases public awareness of the importance of legal protection in MSME management.